A negatively curved nanographene with four embedded heptagons - Elbert, Sven; Paine, Owen T. A.; Kirschbaum, Tobias; Schuldt, Moritz P.; Weber, Laura; Rominger, Frank; Mastalerz, Michael (Journal of the American Chemical Society, 2024)
Negatively curved nanographenes are considered as cutouts of three-dimensional fully sp2-hybridized carbon allotropes such as Schwarzites. Here we present the synthesis of a C76 cut-out of the Schwarzite 8-4-1-p proposed by Lenosky et al. and investigate its optical as well as electrochemical properties. Furthermore, supramolecular interactions with fullerenes C60 and C70 were studied.
Gesehen am 26.02.2025